Verification of the 'desakota' concept, assessment of land use and environmental problems, and related policy implications : case study of the Northern Corridor, Bangkok, Thailand - Iqbal, Javaid; Robinson, Ira. M.; Kammeier, Hans Detlef; Amin, A.T.M. Nurul; Ministry of Defence, Government of Pakistan (Bangkok : Asian Institute of Technology, 1990)
This study verifies the concept of 11 desakota 11 regions by studying Khlong Luang and Nang Sua districts of Pathumthani Province of Bangkok Metropolitan Region (BMR), Thailand . The study assesses the benefits and problems due to uncontrolled development of industries in "Northern Corridor" area and the present government policies. It was based both on primary and secondary sources of information. Primary data was collected from six villages with three from each district . Results of the study shows strong impacts of industrial development of "Northern Corridor" on employment, income, and mobility of the rural households of Khlong Luang district whereas impacts on rural households of Nang Sua district are negligible. Analysis of land use and environmental problems shows that mainly mixed development of different land uses is taking place on either side of the highway in the form of ribbon development due to the lack of secondary and feeder roads with least control and almost no zoning of residential and industrial development f r om the government agencies. Environmental condition is generally poor and characterized by severe pollution of water ways. Based on the analysis of primary and secondary data it was concluded that Khlong Luang district possesses a ll the characteristics of 11 desakota11 regions whereas Nong Sua district does not fall under the definition of 11 desakota 11 {u2022} From the analysis of the present government policies, it wa s concluded that present policies are not linked with the required changes/ improvements in the existing administrative structure. Based on the above conclusions three major policy measures were recommended . These emphasis on use of infrastructure as a planning tool to guide the future growth, necessary changes in the present land taxation system to avoid scattered land development, and adaptation of land pooling/readjustment technique for opening up of certain areas for urban development .
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1990
Keywords: Land use, Urban -- Thailand -- Pathum Thani